Nanotecnologia: novas formas de trabalhos e os riscos para o trabalhador - Silva, Marylad Medeiros da (2018)
The technology has been the space of the plurality of ideas, inventions which have influenced the labor market from its innovations that often do not calculate the consequences in the short or long term, chasing, especially in the area of health, the benefits snapshots it can bring. With this in mind, this dissertation aims to analyze nanotechnology from its contributions, but mainly focusing on the impacts that it can cause to the worker who is directly affected by the handling of their substances and, consequently, the environment when it comes of a larger scale, taking into consideration that society will also suffer over time from the damages caused in nature. In this perspective, it is proposed an analysis of the legislation in a macro aspect when analyzing the Federal Constitution, the Principles of Environmental Law and the Law of the worker, considering that there is still no specific regulation that can protect these professionals. It is also proposed to analyze, in the light of ethics, the precautionary principle and prevention, in order to contribute to this possible regulation, without the intention of ending the debate, but of opening up even more space for the discussion of the subject in question.